Biofilm production and resistance to disinfectants in Salmonella strains isolated from prickly pear, water and soil - De los Santos Villamil, Alfricia Adriana; Hernández Anguiano Ana María; Eslava Campos, Carlos Alberto; Landa Salgado, Patricia; Mora Aguilera, Gustavo; Luchansky, John Bernard (Revista Mexicana de Ciencias Agrícolas, 2018)
A characteristic from Salmonella is its capacity to form biofilms. These structures can become sources of contamination in the production of safe food, as they resist treatment with antibiotics and are difficult to remove in normal cleaning procedures. Therefore the objectives of this study were: 1) determine the capacity of Salmonella strains isolated from prickly pear (10 strains), water samples (2 strains) and soil (3 strains) to form biofilms and 2) evaluate the bactericidal effect of disinfectants citric acid, lactic acid and sodium hypochlorite on biofilm- forming strains. We used the method of O’Toole and Kolter (1998) and polystyrene plates (Coster®) with minimal essential medium with glucose (MEM) and determined the optical density (OD) to estimate the production of biofilms. The disinfectants were applied to plates with biofilm formation in simple MEM 48 h at 37 °C.All strains showedbiofilmproductionafter24halthoughtherewere significant differences (Tukey α= 0.05), depending on the incubation time with respect to the values of OD. The soil strains expressed it’s the capacity faster than water and prickly pear. Sodium hypochlorite (200 ppm) and lactic acid (1.5 x 10-4) inhibited cell growth when applied for 20 min on biofilms. The results obtained demonstrate the importance of implementing good agricultural practices in the production of prickly pear as a strategy to prevent contamination by Salmonella strains biofilms forming in vivo, where the effect of treatment with sanitizers may vary.